Legal Protection of Independent Shareholders Affected By Suspension From The Indonesia Stock Exchange - Erlina Erlina; Darminto Hartono Paulus (Eduvest - Journal of Universal Studies, 2022)
Sanctions for temporary suspension (suspense) of trading against the company PT. Garuda Indonesia which receives sanctions from the Indonesia Stock Exchange (IDX) if it is related to the regulation of stock suspense in IDX Regulation Number 1-H concerning sanctions (Appendix to the Decree of the Director of PT Bursa Efek Jakarta Number: Kep-307 / BEJ / 07-2004. The regulation regarding incomplete stock suspense sanctions in IDX regulation Number 1-H regarding sanctions has the potential to cause losses to independent shareholder investors because it is not equipped with violation criteria that can be subject to stock suspense sanctions. Based on this background, there is a formulation of the problem as follows: How to regulate stock trading suspense sanctions for companies subject to suspense sanctions; How is the legal protection for shareholders who are subject to stock trading suspense sanctions by the Indonesia Stock Exchange. This research uses normative juridical research methods, with a statutory approach and a conceptual approach, using primary, secondary and tertiary legal materials which are analyzed using descriptive techniques and interprestaation techniques. The results of this study show that legal protection for investors affected by stock suspense consists of preventive legal protection and repressive legal protection. Preventive legal protection is preventive, namely by implementing the principle of openness (Disclosure Principle). Meanwhile, repressive legal protection is to provide recovery in the form of compensation where independent shareholders can file a lawsuit if the company's directors are deemed negligent and cause losses to the company.